1995
DOI: 10.1111/j.1502-3931.1995.tb01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical analysis of Late Silurian brachiopod faunas, chiefly from Asia and Australia

Abstract: Shallow water benthic marine invertebrates (such as brachiopods from Benthic Assemblages [BA] 1–3) have usually played a much more important role than deeper ones (BA 4–5 or even deeper) in evaluating biogeographical provincialism in geological history. The Silurian brachiopod Retziella Fauna, characterized by the common presence of Retziella in association with various provincial taxa and many common North Silurian Realm genera, is known from southwest Tienshan, North China, South China, North Vietnam, and Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…During Middle-Late Ordovician times, the SIB had rifted from the northern margin of East Gondwana and the Changning-Menglian Proto-Tethys Ocean had formed at least since the Middle Ordovician (Figure 9b), such as the presence of~470 Ma oceanic cumulate gabbros in the CMSZ (Wang, Luo, et al, 2016;Wang, Wang, Pan, et al, 2013). However, considering the fact that these continental blocks have Sino-Australian province faunas in the Early Paleozoic (Metcalfe, 2013;Rong et al, 1995), it is likely that they were not far away from the northern Australian Gondwana and remained in the same latitude range at that time. In this respect, a narrow Changning-Menglian Proto-Tethys Ocean can most likely account for their similar province faunas in the Early Paleozoic.…”
Section: 1029/2019tc006028mentioning
confidence: 99%
“…During Middle-Late Ordovician times, the SIB had rifted from the northern margin of East Gondwana and the Changning-Menglian Proto-Tethys Ocean had formed at least since the Middle Ordovician (Figure 9b), such as the presence of~470 Ma oceanic cumulate gabbros in the CMSZ (Wang, Luo, et al, 2016;Wang, Wang, Pan, et al, 2013). However, considering the fact that these continental blocks have Sino-Australian province faunas in the Early Paleozoic (Metcalfe, 2013;Rong et al, 1995), it is likely that they were not far away from the northern Australian Gondwana and remained in the same latitude range at that time. In this respect, a narrow Changning-Menglian Proto-Tethys Ocean can most likely account for their similar province faunas in the Early Paleozoic.…”
Section: 1029/2019tc006028mentioning
confidence: 99%
“…As a consequence, these authors suggested that the two main units were connected at least during Ordovician‐Silurian time (Figure 17a). This assertion is further supported by (a) similarities of Ordovician‐Silurian conodont and brachiopod species found in the CTS, STS and northern Tarim regions (Rong et al., 1995; Z. H. Wang et al., 2007b) and (b) absence of older than Silurian ophiolites between the CTS and NE Tarim. In these regards, a Tarim‐CTS connection during, at least, early Paleozoic time can be established.…”
Section: Discussionmentioning
confidence: 76%
“…развитыми в Северной Японии в горах Китаками (свита Каваути). Однако там встречаются другие брахиоподы [39], принадлежащие, вероятно, Сино-Австралийской провинции [38]: Skenidioides kitakamiensis Tachib., Aegiria sugiyamai Tachib., Salopina onukii Tachib., Atrypina kitakamiensis Tachib., Endospirifer nipponicus Tachib.…”
Section: Introductionunclassified